ANALISIS SEMIOTIK DALAM LIRIK LAGU “SELALU ADA DI NADIMU” KARYA LALEILMANINO - Mutia Sari Devi; Nesha Putri Pratama (SUAN PUBLISHER, 2026)
This study analyzes the lyrics of Selalu Ada di Nadimu by LALEILMANINO using Ferdinand de Saussure's semiotic approach. The research aims to explore the profound meaning of each lyric stanza as a medium of emotional communication between the songwriter and the listeners. Employing a qualitative method, the lyrics are divided into several stanzas for analysis based on the concepts of signifier and signified. The findings reveal that the lyrics convey messages of optimism, sincerity, and resilience in facing life's challenges, with prayers serving as an eternal expression of a mother's love for her child, even after worldly separation. This song serves not only as entertainment but also as a medium to deliver deep spiritual and emotional values. This study is expected to serve as a reference for other semiotic studies, particularly in analyzing the meaning of song lyrics as a form of artistic communication.